Takotsubo Cardiomyopathy Coexisting with Acute Pericarditis and Myocardial Bridge - Seyed Hashem Sezavar; Neda Toofaninejad; Shokoufeh Hajsadeghi; Hassan Riahi Beni; Reza Ghanavati; Marjan Hajahmadi; Morteza Hassanzadeh (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TCM) is a stress-induced cardiomyopathy that occurs primarily in postmenopausal women. It mimics clinical picture of acute coronary syndrome with nonobstructive coronary arteries and a characteristic transient left (or bi-) ventricular apical ballooning at angiography. The exact pathogenesis of TCM is not well recognized. Hereby we present an unusual case of TCM that presents with signs and symptoms of acute pericarditis and was also found to have a coexisting coronary muscle bridge on coronary angiography. We discuss the impact of these associations in better understanding of the pathogenesis of TCM.